Heroic history of the Institute of Epidemiology and Microbiology (1941–1945) and the main achievements of the present time - G. A. Danchinova; S. I. Kolesnikov; L. I. Kolesnikova; O. B. Ogarkov; L. V. Rychkova (Acta Biomedica Scientifica)
The aim of this article was to show the labor valour during the Great Patriotic War of the employees of the first research institute in Irkutsk, which began its history in 1912, as well as their success of the present time. The oldest scientific institution in the Irkutsk region was originally created on the initiative of the Siberian Medical Society as a laboratory and was transformed into the Chemical and Bacteriological Institute in 1918, and in 1930 it became the Institute of Epidemiology and Microbiology of the People’s Commissariat of Public Health of Russia.By the beginning of the Great Patriotic War, the institute had an epidemiological department and a microbiological laboratory that carried out epidemiological surveillance and diagnosis of a wide range of infections in Siberia. During the war years, the manufacturing sector with the production of vaccines and serums acquired particular importance. By the end of the war, 285 employees worked at the institute, 32 of them had higher education. During the war years, the production of vaccines against typhoid, paratyphoid, dysentery, diphtheria, tuberculosis, and smallpox was significantly increased. Serums against tetanus and measles, and a dysentery bacteriophage were produced. At the same time, research projects and thesis works were carried out. The employees of the institute received national and departmental awards, commendations, honorary distinctions, and rewards for their scientific work and production excellence.Currently, the institute continues the glorious traditions of the past and demonstrates truly heroic efforts in the development of virology and microbiology, working in priority areas of medical and biological science. Of course, the works of scientists of the present time will be appreciated only by descendants, as is now happening with the assessment of the work of the Institute of Epidemiology and Microbiology during the Great Patriotic War.